Discovery of Novel Autophagy Inhibitors and Their Sensitization Abilities for Vincristine‐Resistant Esophageal Cancer Cell Line Eca109/VCR - Shan, Changyu; Hui, Wenqi; Li, Hongwei; Wang, Zheng; Guo, Chunling; Peng, Ruikun; Gu, Jing; Chen, Yingchun; Ouyang, Qin (ChemMedChem, 2020)
Resistance phenomena, especially acquired drug resistance, have been severely hampering the application of chemotherapeutics during cancer chemotherapy. Autophagy plays a role in maintaining the survival of cancer cells and might mediate resistance to chemotherapy drugs. Herein, a new series of 5‐amino‐2‐ether‐benzamide derivatives were synthesized and evaluated as autophagy inhibitors. Selected from 14 synthesized compounds as lead autophagy inhibitor, N‐(cyclohexylmethyl)‐5‐(((cyclohexylmethyl)amino)methyl)‐2‐((4‐(trifluoromethyl)benzyl)oxy)benzamide (4 d) showed the most obvious effect of LC3B protein conversion. Further, its autophagy inhibition, evaluated by using transmission electron microscopy and confocal microscopy, showed that the fusion of autophagosomes and lysosomes in the final stage of autophagic flux was suppressed. We also found that 4 d could enhance the chemosensitivity of vincristine in vincristine‐resistant esophageal cancer cell line Eca109/VCR in a synergistic, associative manner. Moreover, a computational study showed that 4 d might bind with p62‐zz to inhibit autophagy. We also found 4 d to be relatively less cytotoxic to normal cells versus cancer cells than the reported p62‐zz inhibitor. Enhanced chemosensitivity: A new series of 5‐amino‐2‐ether‐benzamide derivatives has been synthesized, and their autophagy inhibition has been evaluated. The synthesized compounds significantly enhanced the chemosensitivity of vincristine in vincristine‐resistant esophageal cancer cell line Eca109/VCR. A similarity search and molecular docking revealed that the p62‐zz domain might be the binding target.